Regional Inequality in Daerah Istimewa Yogyakarta Province 2014-2024: A William Index Analysis - Khofifah Ghomzah; Faza Safira Mahardika Putri; Berliana Ranti Fara Fauziah (Journal of Developing Economies, 2025)
Objective: Economic growth is an important aspect that reflects the success of a country or region’s economic development. The economy of Yogyakarta Province tends to increase from 2014 to 2024 based on the increasing GRDP per capita data, but there is still a problem of inequality. Income inequality between regions can lead to development problems and economic instability. The purpose of this study is to determine the level of inequality between regencies/cities in Yogyakarta Province from 2014 to 2024. This study includes empirical studies that make important contributions by providing the latest empirical evidence on the condition of regional inequality in the Special Region of Yogyakarta and by analyzing the characteristics of economic growth in the region. Methods: The data used in this study is time series data from the Gross Regional Domestic Product per capita and Total Population of Regency/City in the Province of DIY for the period 2014-2024. To determine and analyze inequality, the Williamson Index is used. indings: The average inequality between regions in DIY Province is 0.8296, which, according to the criteria (WI > 0.5), indicates a high level of inequality between regencies/cities. This value indicates that inequality among the regencies/cities in Yogyakarta Province is high, or economic growth between regions is uneven. Originality/Value: This study provides updated evidence for Yogyakarta’s unique context. This study offers a novel approach by extending the analysis period to 11 years, from 2014 to 2024, including the latest data. Policy Implication: Recommendations include evaluating and reformulating strategic policies for economic development based on leading sectors, prioritizing equitable infrastructure development, improving access to education and healthcare, and fostering potential sector development in underdeveloped areas to reduce regional disparities.